CRYPTOSPORIDIOSIS AMONG CHILDREN OF DISTRICT SKARDU, PAKISTAN - Khushdil, Arshad; Murtaza, Fatima; Chattha, Mazhar Nazir (Journal of Ayub Medical College Abbottabad, 2016)
Background. Cryptosporidiosis is a common cause of persistent diarrhoea in children in developing countries. Previously it was thought to be a major pathogenic organism in immuno-compromised children, but recent studies have shown it to be a common infectious agent in immune-competent children as well. Methods. This descriptive case-series was carried out at Combined Military Hospital Skardu, Pakistan from August 2014 to June 2015. 53 children aged 12 months to 12 years with history of persistent watery diarrhoea for more than 2 weeks, with no blood or mucous in it and no other systemic findings, were included in the study. Results. We examined 53 stool specimen from children with persistent diarrhoea for the presence of cryptosporidium as well other pathogenic organisms. There were 22 (41.5%) females and 31 (58.5%) males. Out of 53 samples, 11 (20.8%) samples were found to be positive for cryptosporidium. Twenty-seven (50.9%) samples were found to be negative for any intestinal pathogen. Conclusion. It is concluded from this study that cryptosporidium is a very common infectious organism of persistent diarrhoea in this part of the country. Keywords. Persistent diarrhoea, cryptosporidium, ascariasis